Migração e políticas públicas municipais: uma análise das ações em Matelândia/PR - Brachtvogel, Vanessa (2025)
This research aims to analyze the role of the Municipality of Matelândia/PR in the formulation and implementation of public policies directed at migrants. The study is based on the author's experience as a municipal public servant and on the needs identified within the municipality. The adopted methodology is qualitative with a descriptive focus, employing bibliographic, documentary, and ethnographic research, in addition to technical visits to the municipal departments of health, education, social assistance, and labor. The research is structured into three chapters: the first addresses the population formation of the municipality and the existing migration-related legislation; the second examines the services provided by the Municipality of Matelândia in the main areas of public policy, namely education, health, labor, and social assistance; and the third analyzes reception protocols and proposes concrete actions for municipal government engagement, based on the experiences of other municipalities and the needs expressed by migrants. The study concludes that, although there are occasional efforts, significant gaps remain in the care provided to migrants, highlighting the need for the development of structured and inclusive public policies in the Municipality of Matelândia.